TAK1 Regulates Cartilage and Joint Development via the MAPK and BMP Signaling Pathways - Gunnell, Lea M (Wiley Subscription Services, Inc., A Wiley Company, 2010)
The importance of canonical transforming growth factor β (TGF-β) and bone morphogenetic protein (BMP) signaling during cartilage and joint development is well established, but the necessity for noncanonical (SMAD-independent) signaling during these processes is largely unknown. TGF-β activated kinase 1 (TAK1) is a MAP3K activated by TGF-β, BMP, and other mitogen-activated protein kinase (MAPK) signaling components. We set out to define the potential role for noncanonical, TAK1-mediated signaling in cartilage and joint development via deletion of Tak1 in chondrocytes (Col2Cre;Tak1(f/f)) and the developing limb mesenchyme (Prx1Cre;Tak1(f/f)). Deletion of Tak1 in chondrocytes resulted in novel embryonic developmental cartilage defects including decreased chondrocyte proliferation, reduced proliferating chondrocyte survival, delayed onset of hypertrophy, reduced Mmp13 expression, and a failure to maintain interzone cells of the elbow joint, which were not observed previously in another Col2Cre;Tak1(f/f) model. Deletion of Tak1 in limb mesenchyme resulted in widespread joint fusions likely owing to the differentiation of interzone cells to the chondrocyte lineage. The Prx1Cre;Tak1(f/f) model also allowed us to identify novel columnar chondrocyte organization and terminal maturation defects owing to the interplay between chondrocytes and the surrounding mesenchyme. Furthermore, both our in vivo models and in vitro cell culture studies demonstrate that loss of Tak1 results in impaired activation of the downstream MAPK target p38, as well as diminished activation of the BMP/SMAD signaling pathway. Taken together, these data demonstrate that TAK1 is a critical regulator of both MAPK and BMP signaling and is necessary for proper cartilage and joint development. © 2010 American Society for Bone and Mineral Research.